An outline on distribution and hosts of the cystoid nematodes of Ataloderinae Wouts, 1973 and Meloidoderinae Golden, 1971 - Ghaderi, Reza (Zootaxa, 2019)
The cystoid nematodes of the subfamilies Ataloderinae and Meloidoderinae include 32 recognized species belonging to 10 genera. The geographical distribution and preferred hosts of these nematodes are reviewed in the present paper. Most genera in Ataloderinae are believed to have evolved in North America, but some genera currently show different or wider distributions. Although members of Bellodera, Ekphymatodera, Rhizonemella and Sarisodera have only been recovered from North America, those of Atalodera may be found in both North America and South America. Species of the other genera tend to occur in different geographical locations: Cryphodera species have been recorded in Asia and Oceania while Camelodera and Hylonema species have only reported from Asia and Africa, respectively. Members of Meloidoderinae (Meloidodera spp.) are distributed in North America, Asia and Europe. Plant hosts for the cystoid nematodes are distributed among both monocots and dicots. Nematologists suggest an ancient origin for genera such as Meloidodera, Cryphodera and Rhizonemella which can parasitize gymnosperms.